PERANCANGAN SISTEM INFORMASI JASA LAUNDRY PADA LAA LAUNDRY JAMBI - Valencia, Valencia; Purnama, Benni; sandra, Dodi (LPPM Universitasdiwangsa Jambi, 2021)
Laundry is one of the businesses located in Jambi City. Transaction data processing is still donemanually which is written in a notebook. So that the recap of transaction data every month takes arelatively long time, and laundry owners need more time to find consumer goods. Therefore, this studyaims to provide solutions to the problems that occur by offering a laundry service information systemusing the PHP programming language and MySQL DBMS. For system development using the waterfallmethod and system modelings using use case diagrams, activity diagrams, and class diagrams. The resultof this study is a system that can provide good service in manage transaction data, and displaysappropriate and accurate reports to facilitate Laa Laundry in obtaining information.